SEPIC and Flyback Converters for Isolated Photovoltaic Battery Charging Application - Tan N.M.L.; Savi F.; Buticchi G.; Ahmad S.; Gerada C. (Institute of Electrical and Electronics Engineers Inc., 2023)
Charging (batteries); DC-DC converters; Lithium-ion batteries; Accumulator; Charge controllers; Design Methodology; Dissipative snubbers; Flyback converters; Isolated dc/dc converters; Maximum Power Point Tracking; Performance; Photovoltaics; Single-ended; Maximum power point trackers